Biodiesel synthesis using integrated acid and base catalysis in continuous flow. Issue 26 (30th June 2016) - Asadi, Mousa; Hooper, Joel F.; Lupton, David W.
Abstract: The use of biodiesel derived from oils and fats is making an increased contribution as a renewable energy source. The synthesis of biodiesel involves transesterification of triglycerides to the monoalkyl esters, a process often made challenging by the presence of free fatty acids (FFA). Herein an integrated flow system for the synthesis of biodiesel, employing a solid supported acid catalyst for esterification of FFAs, followed by transesterification using polymer supported N -heterocycle carbene (NHC) catalyst is reported. This system delivers biodiesel in high yields from a variety of fat and oils, using robust and recyclable catalysts. Graphical abstract: